Ditched : a love story - Mellom, Robin (Hyperion, 2013)
Justina wakes up in a ditch in the middle of the night after attending her senior prom and struggles to piece together the events--which seem to involve a three-legged Chihuahua, a demolition derby-ready Cadillac, and a fresh tattoo--that brought her there.